Anti‐desmocollin autoantibodies in nonclassical pemphigus. (1st July 2015) - Ishii, N.; Teye, K.; Fukuda, S.; Uehara, R.; Hachiya, T.; Koga, H.; Tsuchisaka, A.; Numata, S.; Ohyama, B.; Tateishi, C.; Tsuruta, D.; Furumura, M.; et al.
Summary: Background: Despite the established pathogenic role of anti‐desmoglein (Dsg) antibodies in classical pemphigus, the significance of autoantibodies to another desmosomal cadherin, desmocollin (Dsc) is at present unknown. No consistent immunoassay for immunoglobulin (Ig) G autoantibodies to Dscs has been developed. Objectives: The aim of this study was to develop reliable assays to detect anti‐Dsc autoantibodies. Methods: We expressed soluble recombinant proteins (RPs) of human Dsc1–3 in mammalian cells and examined sera of various types of pemphigus, including 79 paraneoplastic pemphigus (PNP) sera, by novel enzyme‐linked immunosorbent assays (ELISAs) using the RPs. We also performed ELISAs of Dsc baculoproteins and used the complementary DNA (cDNA) transfection method, and compared the results with those of mammalian ELISAs. Results: Through mammalian ELISAs, IgG autoantibodies to Dsc1, Dsc2 and Dsc3 were detected in 16·5%, 36·7% and 59·5% of PNP sera, respectively, and considerable numbers of pemphigus herpetiformis (PH) and pemphigus vegetans (PVeg) sera reacted strongly with Dsc1 and Dsc3. Mammalian ELISAs were highly specific and more sensitive than baculoprotein ELISAs or the cDNA transfection method. Several Dsc‐positive sera, particularly PH sera, showed no reactivity with Dsgs. The reactivity of PNP serum and PVeg serum with Dscs was not abolished by pre‐absorption with Dsg RPs. Conclusions: The results of these novel ELISAs indicated that IgG anti‐Dsc autoantibodies were frequently detected and potentially pathogenic in nonclassical pemphigus.